Karakteristik Morfologi dan Organ Reproduksi pada Bebek Betina - Hasibuan, Febry Rahmadhani; Wardana Purba, Balqis Putri; Kinanti Rambe, Diva Raya; Mawaddah, Hanifa; Hafizhah, Kayla Nur (Indonesian Journal Publisher, 2023)
This research aims to determine the morphology of female ducks from two different feeds andalso determine the reproductive organs in female ducks. The data collection technique was carried out directly by observing the development of the morphological characteristics of the ducks every week. In this study, two female ducks were used with two different feeds, namely 1 duck eating bran and the other duck eating pellets as the main feed. Based on the observations made, it can be concluded that ducks that eat bran (natural feed) and pellets (artificial feed) have a morphology that is not much different from each other, namely they have a slender body shape and a relatively long neck. The main difference lies only in the diet. and the nutritional quality obtained from the food. The reproductive organs of female ducks are located inside their bodies. The main reproductive organs in female ducks consist of the ovaries, oviducts (egg tubes), and cloaca. The ovaries of female ducks generally have an oval shape like small eggs at the end of the cloaca.